A Consequence of Dispersity on the Self‐Assembly of Amphiphilic Homopolymers Containing Main‐Chain Azobenzene. Issue 12 (15th September 2021) - Hu, An; Shi, Xianheng; Li, Lishan; Zhang, Wei; Zhang, Zhengbiao; Zhou, Nianchen; Zhu, Xiulin
Abstract: The self‐assembly of amphiphilic oligomers/polymers is a versatile and promising approach for creating nonspherical polymeric nanoparticles. Discrete amphiphilic oligomers/polymers with molecularly defined structures are ideal candidates for fabricating smart nanoparticles and for achieving a deeper understanding of structure‐controlled self‐assembly. Herein, discrete and disperse amphiphilic homopolymers of PAZOn TEG2n, with hydrophobic azobenzene are designed and synthesized as the main chains tethered with hydrophilic tetraethylene glycol monomethyl ether (TEG) units, to accurately investigate the impact of dispersity on their self‐assembly in solution. The discrete‐PAZO8 TEG16 in DMF/water and in THF/water results in the formation of 2D lamellae, while the dispersed counterpart prefers to self‐assemble into spherical micelles. The significant difference is due to their distinction between interior structures of assembly. Furthermore, photoisomerization of azobenzene triggers dissociation/reassembly for discrete polymeric nanoparticles but no obvious change for the dispersed counterparts under irradiation with UV/vis light. This work reveals the influence of dispersity on the self‐assembly of amphiphilic polymers and stimuli‐responsive properties of their nanomaterials, which is desirable for universal applicability in fabricating smart 2D lamellas. Abstract : A set of discrete and disperse amphiphilic polymers with specific hydrophobic/hydrophilic ratios are synthesized successfully. Subsequently, the self‐assembly behaviors of discrete and dispersed amphiphilic polymers and the light‐responsive properties of their aggregates are investigated in detail and compared, revealing the influence of dispersity on the self‐assembly and stimuli‐responsive properties of nanomaterials.